Loneliness in Philip K. Dick’s Novel Do Androids Dream of Electric Sheep? - Đorovic, Miljana Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The inhabitants of eerily desolated and bleak San Francisco in Philip K. Dick’s novel Do Androids Dream of Electric Sheep? are all depressed, lonely, isolated, and alienated. The paper strives to analyze the characters of John Isidore, Rick and Iran Deckard, Pris Stratton, and Rachael Rosen, as well as the boundaries between the human and the android based on the notion of inverse parallelism—while humans program their emotions with mood organs and thus are becoming more similar to androids, androids yearn to possess human-like emotions and become humans. The paper argues that it is loneliness that is the prime driving force behind the process of inverse parallelism.
Keywords: Dick; loneliness; humans; androids; empathy box; inverse parallelism; animals